Youngia jiulongshanensis (Asteraceae: Liguliflorae), a new species from Zhejiang, East China - Cai, Xin; Xu, Yue-Liang; Liu, Ju-Lian; Zhou, Hui-Long; Jin, Xiao-Feng (Phytotaxa, 2019)
A new species of Asteraceae, Youngia jiulongshanensis, is described and illustrated from Mount Jiulong, south-western Zhejiang Province of East China. It most closely resembles Youngia heterophylla, but differs in having smaller oblong basal leaves (vs. basal leaves oblanceolate), lateral lobes of leaves 1–2 pairs (vs. 1‒8 pairs), 5‒7(8) florets in each capitula (vs. 11‒25 florets in each capitula), involucre 5‒6 mm long (vs. 6‒7.5 mm long), inner phyllaries 5 (vs. 8). Observations on pollen grains of Youngia jiulongshanensis and Y. heterophylla detect the pollen grains of the new species are significantly larger than those of Y. heterophylla. Sequences of ITS (Internal Transcribed Spacer) and cp DNA demonstrate Youngia heterophylla as the closest extant relative of the new species.